2013
DOI: 10.1016/j.econlet.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Giving and sorting among friends: Evidence from a lab-in-the-field experiment

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…Notably, we do not find evidence that friends sort by trustworthiness unless they observe their friend’s behavior. This finding is in line with the results of Binzel and Fehr (2013), who find that friends do not necessarily shape our altruistic preferences: Result 3 (Updating) . Trustors update their posterior beliefs consistent with their observation: Observing trustworthiness increases their posterior beliefs of trustworthiness in the population; observing defection decreases posterior beliefs.The right panel in Figure 8 plots the observed updating behavior in the experiment.…”
Section: Resultssupporting
confidence: 90%
“…Notably, we do not find evidence that friends sort by trustworthiness unless they observe their friend’s behavior. This finding is in line with the results of Binzel and Fehr (2013), who find that friends do not necessarily shape our altruistic preferences: Result 3 (Updating) . Trustors update their posterior beliefs consistent with their observation: Observing trustworthiness increases their posterior beliefs of trustworthiness in the population; observing defection decreases posterior beliefs.The right panel in Figure 8 plots the observed updating behavior in the experiment.…”
Section: Resultssupporting
confidence: 90%
“…The ones that used dictator games, as we do, did not find statistically significant gender effects (e.g. Binzel and Fehr (2013) in Cairo; Jakiela (2011) in Kenya; Gowdy et al (2003) in Nigeria; Ligon and Schechter (2012) in Paraguay; Ado and Kurosaki (2014) in Jakarta). 2 Second, another line of experimental research has developed around how sharing is influenced by social proximity (Bohnet and Frey, 1999;Charness and Gneezy, 2008).…”
Section: Introductionsupporting
confidence: 43%
“…Thus, individuals care more about the consumption levels of contacts who are closer to them than those who are farther [6,7]. In fact, previous studies have shown that altruism in dictator games is higher toward closer social contacts than distant social contacts [18,[20][21][22][23]. This would predict that individuals' giving to close social contacts is higher than to distant social contacts.…”
Section: Hypothesesmentioning
confidence: 95%